Do white grapes really exist?. (March 2015) - Arapitsas, Panagiotis; Oliveira, Joana; Mattivi, Fulvio
Abstract: Anthocyanins are natural coloured pigments representing part of the protective mechanism of many plants, including Vitis vinifera L., and they have a considerable influence on wine quality. Moreover, the presence of anthocyanins in ripe berries is used as the accepted qualitative parameter for distinguishing red from white grapes, since these pigments are known to be present only in red berries. On the other hand, pyranoanthocyanins are important pigments for the colour stability of red wines and are known to be formed after berry crushing, during vinification and wine ageing. In this work, for the first time we provide clear evidence that the skin of international white grape cultivars (Chardonnay, Sauvignon Blanc and Riesling) contains measurable traces of anthocyanins. In addition, for the first time we report clear proofs about the presence of pyranomalvidin 3- O -glucoside (B-type vitisin) and carboxypyranomalvidin 3- O -glucoside (A-type vitisin) in fresh grapes and we quantify them. Highlights: Anthocyanins were detected and quantified in white grapes. For the first time were detected and quantified pyranoanthocyanins in grape skin. The concentration of all pigments was highly influenced by the climatic changes.